Prevalence of Gestational Diabetes Mellitus and Pregnancy Outcomes in Iranian Women - Arash Hossein-Nezhad; Zhila Maghbooli; Ali-Reza Vassigh; Bagher Larijani (Elsevier, 2007)
Objective: We investigated the prevalence and outcome of gestational diabetes mellitus (GDM) in pregnant Iranian women. Materials and Methods: A total of 2,416 women, who were consecutive referrals for antenatal care to five university teaching hospitals in Tehran, were recruited. Patients with known diabetes were excluded. All 2,416 women were screened with a 50-g 1-hour glucose challenge test, and any woman with a plasma glucose concentration more than or equal to 130 mg/dL was given a 100-g 3-hour glucose tolerance test. Diagnosis of GDM was according to Carpenter and Coustan's criteria. The remainder served as controls for the study. Results: There were 114 women (4.7%; 95% confidence interval [CI], 3.9-5.6%) who had GDM. Women with GDM had a significantly higher parity and body mass index than non-diabetic women. Women with GDM were also more likely to have a family history of diabetes and a history of poor obstetric outcome. Of the 114 women, 27 (23.6%) were younger than 25 years old, and 16 (14.0%) had no recognizable risk factor for diabetes. The odds ratio (OR) for cesarean section (OR, 2.28; p = 0.0002), macrosomia (OR, 1.93; p = 0.0374), neonatal hypoglycemia (OR, 3.2; p = 0.011) and hypocalcemia (OR, 3.045; p = 0.0195), and still birth (OR, 4.8; p = 0.003) were all significantly higher in women with GDM than non-GDM controls. Conclusion: One out of every 20 pregnant Iranian women will develop GDM, with significantly increased odds of adverse maternal and fetal outcome. The significant proportion of young and/or risk factor-free women in our sample means that there seems to be a case for universal GDM screening in pregnant Iranian women.